2017
DOI: 10.1093/nar/gkx718
|View full text |Cite
|
Sign up to set email alerts
|

Functional impacts of 5-hydroxymethylcytosine, 5-formylcytosine, and 5-carboxycytosine at a single hemi-modified CpG dinucleotide in a gene promoter

Abstract: Enzymatic oxidation of 5-methylcytosine (5-mC) in the CpG dinucleotides to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine (5-fC) and 5-carboxycytosine (5-caC) has central role in the process of active DNA demethylation and epigenetic reprogramming in mammals. However, it is not known whether the 5-mC oxidation products have autonomous epigenetic or regulatory functions in the genome. We used an artificial upstream promoter constituted of one cAMP response element (CRE) to measure the impact of 5-mC in a hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 40 publications
4
37
1
1
Order By: Relevance
“…From our data, we found that at regions closest to the TSS (Up1 and FirstEx), both 5mC and 5hmC features correlated negatively with gene expression, although the correlation was stronger for 5mC ( Figure S8). This is consistent with a recent report that both types of DNA methylation could repress gene expression by affecting transcription factor binding at the promoter (Kitsera et al, 2017).…”
Section: Relationship Between Transcript Body Methylation and Expressionsupporting
confidence: 93%
“…From our data, we found that at regions closest to the TSS (Up1 and FirstEx), both 5mC and 5hmC features correlated negatively with gene expression, although the correlation was stronger for 5mC ( Figure S8). This is consistent with a recent report that both types of DNA methylation could repress gene expression by affecting transcription factor binding at the promoter (Kitsera et al, 2017).…”
Section: Relationship Between Transcript Body Methylation and Expressionsupporting
confidence: 93%
“…S12). This is consistent with a recent report that both types of DNA methylation could repress gene expression by affecting transcription factor binding at the promoter (Kitsera et al 2017). Inside the transcript body, 5hmC tended to correlate more positively with gene expression than did 5mC in normal liver samples, but the reverse is observed for some liver and lung tumor samples.…”
Section: Relationship Between Transcript Body Methylation and Expressionsupporting
confidence: 92%
“…[96] The discovery that the mammalian TDG enzyme removes fdC and cadC,c reates therefore the overarching idea that base excision repair and epigenetics are connected processes that allow regulation of transcriptional activity. [20,97] Another possibility is that fdC has independent epigenetic functions.T his would be in line with interaction data that revealed distinct reader proteins for hmdC and also fdC as well as cadC. [98,99] Of interest in this context are several analyses of genomic fdC profiles showing alink between the presence of fdC and epigenetic tuning at regulatory elements, such as enhancers and promoters.…”
Section: Hmdc Levels In Tumorsmentioning
confidence: 99%